Savings from Natural Resource Revenues in Developing Countries: Principles and Policy Rules - Paul Collier (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
Many poor countries are now discovering valuable non-renewable natural resources. Unlike most other sources of tax revenue, the government revenues from the depletion of these resources are both unsustainable and volatile. Each of these features implies that the savings rate appropriate for resource revenues should differ from that on other revenues. Further, a discovery is 'news', requiring a transition from a situation which has suddenly become sub-optimal. Such transitions must be expected to generate costs which will themselves affect the optimal savings rate. While the features themselves have long been wellunderstood, the implications for optimal savings behaviour are surprisingly underdeveloped. A fortiori, the implications for the rules which might be the practical embodiment of these analytic underpinnings are also underdeveloped.
Keywords: C31; C53; O13; Q38; 330